2016
DOI: 10.1080/1828051x.2016.1147336
|View full text |Cite
|
Sign up to set email alerts
|

Energy requirements for the maintenance and growth of Dorper-Jinzhong crossbred ram lambs

Abstract: The sheep industry in China has been rapidly developing in recent years; however, the animals' nutritional requirements under certain conditions have not been thoroughly defined. The objective of this study was to investigate the energy requirements of both the maintenance and growth of Dorper-Jinzhong crossbred ram lambs. Thirty 1/2 Dorper  1/2 Jinzhong crossed F1 ram lambs (35 6 0.5 kg of body weight, BW) were randomly selected and divided into five groups in a randomised design for a comparative slaughter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Metabolizable energy (ME) intake and retained energy (RE) as the change in body energy content of animals are measured through this procedure. The slope of linear regression between RE and ME intake indicates efficiency of ME utilization or ME for gain (Chizzotti et al, 2007;Zhao et al, 2016). Both methods require relatively sophisticated research facilities and financial resources to perform the experiments in which these are among the main obstacles in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolizable energy (ME) intake and retained energy (RE) as the change in body energy content of animals are measured through this procedure. The slope of linear regression between RE and ME intake indicates efficiency of ME utilization or ME for gain (Chizzotti et al, 2007;Zhao et al, 2016). Both methods require relatively sophisticated research facilities and financial resources to perform the experiments in which these are among the main obstacles in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…La retención de energía (RE) corresponde a la diferencia entre el contenido inicial y final de energía del cuerpo de los animales (Zhao et al, 2016). Los valores se expresaron con relación al peso metabólico (kcal/kg PV 0.75 ).…”
Section: Retención De Energíaunclassified
“…En el presente caso, se requieren 9.2 kcal de energía metabolizable por cada gramo de ganancia de peso vivo en llamas, y 11.4 kcal en alpacas. Estos resultados son mucho mayores a los valores reportados para ovinos, caprinos y vacunos (Salah et al, 2014), indicando que las llamas y alpacas alimentadas con dietas de forrajes utilizan mayores cantidades de energía metabolizable por cada unidad de ganancia de peso vivo, evidenciando su menor eficiencia para convertir la energía del alimento en carne, con relación al ovino productor de carne (Zhao et al, 2016).…”
Section: Requerimientos De Energía Metabolizable De Ganancia De Pesounclassified
“…Dorper breed is specialized for meat production and is characterized by hardiness, early sexually maturity, rapid growth and excellent meat quality [ 6 ]. To improve growth performance and carcass quality, Dorper sheep have recently been introduced in Shanxi to crossbreed with Jinzhong sheep, and Dorper × Jinzhong crossbreed has become the dominant crossbreed for lamb production in Shanxi [ 7 ]. Nevertheless, the diets formulated for sheep in China are based on information recommended by international committees on animal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the diets formulated for sheep in China are based on information recommended by international committees on animal nutrition. A recent study of Dorper × Jinzhong crossed ram lambs suggested that energy requirements are lower than the requirements recommended by the National Research Council (NRC) and Agricultural and Food Research Council (AFRC) [ 7 ], and therefore, it is expected that mineral requirements will also vary from AFRC recommendations.…”
Section: Introductionmentioning
confidence: 99%